Metamagical themas - "Hofstadter, Douglas R." (England, 1985)
Metamagical themas the Pulitzer Prize winning author of Godel, Escher, Bach for the first time collects his various brilliant essays, most of them originally published in Scientific American and weaves them together with elaborate postscripts.
Keywords: Intellect